Three-dimensional simulations of neutrino-driven core-collapse supernovae from low-mass single and binary star progenitors. Issue 3 (22nd January 2019) - Müller, Bernhard; Tauris, Thomas M; Heger, Alexander; Banerjee, Projjwal; Qian, Yong-Zhong; Powell, Jade; Chan, Conrad; Gay, Daniel W; Langer, Norbert
ABSTRACT: We present a suite of seven 3D supernova simulations of non-rotating low-mass progenitors using multigroup neutrino transport. Our simulations cover single star progenitors with zero-age main-sequence masses between 9.6 and 12.5 M_ and (ultra)stripped-envelope progenitors with initial helium core masses between 2.8 and 3.5 M_ . We find explosion energies between 0.1 and 0.4 Bethe, which are still rising by the end of the simulations. Although less energetic than typical events, our models are compatible with observations of less energetic explosions of low-mass progenitors. In six of our models, the mass outflow rate already exceeds the accretion rate on to the proto-neutron star, and the mass and angular momentum of the compact remnant have closely approached their final value, barring the possibility of later fallback. While the proto-neutron star is still accelerated by the gravitational tug of the asymmetric ejecta, the acceleration can be extrapolated to obtain estimates for the final kick velocity. We obtain gravitational neutron star masses between 1.22 and 1.44 M_, kick velocities between 11 and 695 km s^-1, and spin periods from 20 ms to 2.7 s, which suggest that typical neutron star birth properties can be naturally obtained in the neutrino-driven paradigm. We find a loose correlation between the explosion energy and the kick velocity. There is no indication of spin–kick alignment, but a correlation between the kick velocity and the neutron star angular momentum, which needs to be investigated further as a potential point of tension between models and observations.